THE HERPETOFAUNA OF THE GOLD MINING PROJECT AREA IN NORTH SUMATRA: SPECIES RICHNESS BEFORE EXPLOITATION ACTIVITIES - Hellen - Kurniati (Masyarakat Zoologi Indonesia, 2007)
Kurniati, H. 2007. The herpetofauna of the gold mining project area in NorthSumatra: Species richness before exploitation activities. Zoo Indonesia 16 (1): 1-11. Field surveys of herpetofauna (amphibians & reptiles) were conducted in andaround the PT Newmont Horas Nauli Martabe Project Area for 23 days prior theexploration. Surveys involved visual observations, light attraction, hand collection andtrapping in all major amphibian and reptile habitats. A total of 42 species of amphibiansand 28 species of reptiles (nine snakes, 16 lizards & three turtles) were identified.Based on interviews with local people at Batang Toru Village, there was reliableobservation of two additional species of turtle (Cyclemys dentata & Manouria emys)and one species of snake (Python curtus). Of the more than 42 amphibians speciesand 28 reptile species observed, 12 represented unknown species (10 frogs & twoskinks); one frog species (Occidozyga laevis) might be a new record for Sumatra.Similarity index calculations indicated that herpetofauna diversity at the six sites wasdivided between forested and heavily disturbed habitat.